Exploring the determinants of self-directed learning among medical undergraduates: A qualitative study - Usha Krishnan; Thyagarajan Ravinder; Therese Mary Dhason; Suganthi Manikesi; Devi Chithsabesan; Dorairaj Kalpanaraj (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The National Medical Council has recognized the importance of self-directed learning (SDL) for medical graduates and it has been included as one of the competencies for Indian Medical Graduates. The present study was conducted to explore different determinants, and the factors facilitating and deterring of SDL among medical undergraduates. MATERIALS AND METHODS: This cross-sectional qualitative study was conducted with 40 phase 2 MBBS students and data were collected through focused group discussions over a period of four weeks. A content analysis approach was used in the analysis. RESULTS: The participants included 23 women (58%) and 17 men (42%). The study revealed three main themes and six sub-themes as factors deterring SDL. The majority of participants (84%) favored individual learning, while a smaller number preferred team-based learning. DISCUSSION: Cognitive factors emerged as the most common barriers, including problems with initiation and engagement in SDL and the enormous amount of data available. Educational environmental factors, such as heavy workloads and time constraints, as well as frequent assessments, were also identified as barriers. Attitudinal and mental barriers encompassed issues like lack of practical experience, difficulties in adapting to new learning environments, and challenges in concentration and focus. CONCLUSION: Overall, this study fills gaps in our understanding of factors deterring students' engagement in SDL and provides valuable insights for educators and institutions in implementing effective SDL activities. By addressing these barriers, medical education can equip students better to become lifelong learners and meet the evolving demands of the medical profession.